2009
DOI: 10.4104/pcrj.2009.00010
|View full text |Cite
|
Sign up to set email alerts
|

The Asthma Control TestTM (ACT) as a predictor of GINA guideline-defined asthma control: analysis of a multinational cross-sectional survey

Abstract: Aims: To evaluate whether the Asthma Control Test TM (ACT) score is predictive of Global Initiative for Asthma (GINA) guideline-defined classification levels of asthma control. The ACT is a validated, 5-item, patient-completed measure of asthma control with a recall period of four weeks.Methods: Cross-sectional survey comparing ACT score and GINA classification of asthma control among 2949 patients attending primary care physicians and specialists in France, Germany, Italy, Spain, the UK, and the USA. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
0
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 271 publications
(239 citation statements)
references
References 26 publications
8
213
0
18
Order By: Relevance
“…2 Guideline-defined asthma control can be achieved and maintained for the majority of patients in controlled trial settings. [3][4][5] In Vietnam, the GINA guidelines were recently used as the main reference source for the national asthma guidelines. 1 A recent study suggested that the level of asthma control in Vietnam is poorer than expected, with less than 1% of patients studied meeting the definition of asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…2 Guideline-defined asthma control can be achieved and maintained for the majority of patients in controlled trial settings. [3][4][5] In Vietnam, the GINA guidelines were recently used as the main reference source for the national asthma guidelines. 1 A recent study suggested that the level of asthma control in Vietnam is poorer than expected, with less than 1% of patients studied meeting the definition of asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,25,30 A cutoff score of Յ19 was associated with higher risk of adverse asthma outcomes, such as asthma exacerbation 17,31 and urgent health-care utilization. 17,32 With regard to NAEPP EPR-3 guidelines, a score of Ն20 indicates well-controlled asthma, a score of 16 -19 indicates not well-controlled asthma, and a score of Յ15 indicates very poorly controlled asthma.…”
Section: Accuracymentioning
confidence: 99%
“…Опрос с использованием балльной оценки симптомов по опросникам Asthma Control Test (ACT) и Asthma Control Questionnaire (ACQ) является более чувствительным при оценке из-менения уровня контроля симптомов БА [4,5].…”
Section: терапевтический архив 3 2015unclassified